Innocent bystanders? Monetary policy and inequality in the US - Olivier Coibion; Yuriy Gorodnichenko; Lorenz Kueng; John Silvia (Institute for the Study of Labor (IZA), 2012)
We study the effects and historical contribution of monetary policy shocks to consumption and income inequality in the United States since 1980. Contractionary monetary policy actions systematically increase inequality in labor earnings, total income, consumption and total expenditures. Furthermore, monetary shocks can account for a significant component of the historical cyclical variation in income and consumption inequality. Using detailed micro-level data on income and consumption, we document the different channels via which monetary policy shocks affect inequality, as well as how these channels depend on the nature of the change in monetary policy.
Keywords: E3; E4; E5; 330; monetary policy; income inequality; consumption inequality; Geldpolitik; Schock; Gesamtwirtschaftlicher Konsum; Soziale Ungleichheit; Einkommensverteilung; Schätzung; USA